1984
DOI: 10.1203/00006450-198408000-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Distribution and Determinants of Myocardial Blood Flow during Asphyxia in the Fetal Lamb

Abstract: SummaryThe syndrome of hypoxemia-related myocardial dysfunction in the newborn is generally associated with severe intrapartum asphyxia. We investigated the changes in total and regional distribution of myocardial blood flow (MBF) that occur during asphyxia and the factors that regulate MBF, in the chronically prepared, near term, fetal lamb. Studies were done in the awake, physiologically stable state 36-72 h after surgical preparation.In utero asphyxia was produced by partial cord occlusion and blood flow to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1991
1991
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…Finally, one potential limitation of our study was that it was performed under general anesthesia and open-chest conditions, an approach necessary because of the extent of surgical instrumentation required. However, blood gas data were comparable to those of unanesthetized fetuses, while the average level of mean arterial blood pressure in our study (59 -60 mmHg) was at the upper end of the normal range reported in chronically instrumented late-gestation fetal lambs (1,6,9,19,27,30,33,39,40,42). In addition, LPA flow (70 ml/min) was close to the range of 71-87 ml/min measured with transit-time flow probes in unanesthetized and anesthetized late-gestation fetuses (14,19,33).…”
Section: Discussionsupporting
confidence: 81%
“…Finally, one potential limitation of our study was that it was performed under general anesthesia and open-chest conditions, an approach necessary because of the extent of surgical instrumentation required. However, blood gas data were comparable to those of unanesthetized fetuses, while the average level of mean arterial blood pressure in our study (59 -60 mmHg) was at the upper end of the normal range reported in chronically instrumented late-gestation fetal lambs (1,6,9,19,27,30,33,39,40,42). In addition, LPA flow (70 ml/min) was close to the range of 71-87 ml/min measured with transit-time flow probes in unanesthetized and anesthetized late-gestation fetuses (14,19,33).…”
Section: Discussionsupporting
confidence: 81%
“…However, blood gas and blood pressure data were within the normal range reported in unanesthetized, chronically instrumented late-gestation fetal lambs (1,5,19,22,26,30,33,35,38). It is thus unlikely that the qualitative features of our findings were affected by our experimental approach.…”
Section: Discussionsupporting
confidence: 46%
“…Maintenance of blood pressure is known to occur with chronic growth retardation in animal models, J and an alteration in the distribution of cardiac output and an increase in systemic blood pressure have been described in response to acute occlusion of the umbilical artery in fetal sheep. 4 Our results show that a parallel reduction in both systolic and diastolic shifted-frequencies will produce the expected effect of a relative increase in Doppler indices because D becomes a smaller proportion of S as the values of each approach zero.…”
Section: Discussionmentioning
confidence: 55%